Liquidity Management Framework and Return on Equity: Evidence from Bank of Kigali Plc - Aimable, Sebintu Ruvugwa; Kengere, Osiemo A. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Liquidity management remains a critical determinant of banking performance, yet its specific impact on return on equity (ROE) in Rwanda’s banking sector has received limited empirical attention. This study examines how liquidity management framework components dividend payout, cash flow management, and debt management affect the return on equity of Bank of Kigali Plc, Rwanda’s largest listed bank. An ex-post facto research design was employed using secondary data from audited annual financial statements spanning 2014–2024 (n=11 observations). Multiple regression analysis was conducted using SPSS version 22 to assess the relationship between liquidity management components and ROE. The model specification was ROE = β₀ + β₁ (Dividend Payout) + β₂ (Cash Flow Management) + β₃ (Debt Management) + ε. The liquidity management framework explained 84.7% of the variance in ROE (Adjusted R²=0.847). The model demonstrated statistical significance (F=17.121, p=0.000), confirming that dividend payout, cash flow management, and debt management jointly exert significant effects on ROE. Ordinary dividend (β=1.472, t=2.775, p=0.000), operating activity cash flows (β=0.207, p=0.000), and debt ratio (β=46.793, p=0.000) all contributed meaningfully to ROE variations. Effective liquidity management is integral to maximizing shareholder returns in Rwanda’s banking sector. Strategic dividend policies, robust cash flow optimization, and prudent debt management collectively enhance ROE, supporting the theoretical predictions of Bank Liquidity Requirements Theory and Asset Liability Management Theory. The study highlights the need for banks to optimize liquidity management, maintain appropriate leverage, and adopt transparent practices, while regulators ensure supportive standards. Future research should expand across banks and consider macroeconomic and crisis contexts.